Tunjangan Kinerja Daerah Dan Bangkrutnya APBD Di Sejumlah Daerah - Prayitno, Budi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2011)
Local government effort to improve the welfare of civil servants in local government has been continued to be made. However, this practice allegedly bankrupted precisely Budget Reveneus and expenditures (APBD). As a result of capital expenditures for development cannot run optimally because the budget must be spent for personnel expenditure reached 70 percent. Some things are considered to be causing it is the large number of employees, the absence of clear parameters in determining the nominal standard allowances, and political factors. To that end, the government should immediately find an alternative solution in the short term that is applicable while running a program of bureaucratic reform